(untitled) (Bangladesh Agronomy Journal, 2017)
An experiment was conducted during 20 November 2015 through March 20I6 to assess the effect of planting dates on growth and yield performance of three potential varieties of potato at Plant Physiology research field, Bangladesh Agricultural Research Institute, Gazipur. Three planting dates (November 20, December 5 and December 29) and three varieties (var. BARI Alu-35, BARI Alu-40 and BARI Alu-41) were the treatment variables. The experiment was laid out in a randomized complete block design with three replications. Maximum plant height (42.3 cm) was observed in 5 December sowing in var. BARI Alu-40. Highest number of tuber/plant (13) was recorded from December 5 sowing in var. BARI Alu-41. The highest leaf area was found in December 5 sowing of BARI Alu-40 while the lowest leaf area in November 20 sowing in var. BARI Alu-35. The highest tuber weight/plant (97.25 g) was observed in var. BARI Alu-5 at December 5 sowing and the lowest tuber weight/plant (25.58 g) in var. BARI Alu-35 at November 20 sowing. The maximum potato yield (42.12 t/ha) was obtained at December 5 sowing of BARI Alu-35 followed by same date of var. BARIAlu- 41. From the experiment it was revealed that the first decade of December is the optimum date for planting of potato due to the physiological maturity and tuber yield. Bangladesh Agron. J. 2017, 20(1): 25-29